Analisis Hubungan Belanja Impor terhadap Tabungan Mahasiswa Prodi Pendidikan Ekonomi Stambuk 2024 Universitas HKBP Nommensen Medan - Tri Dian Novita; Leoni Gress Cyntya; Arina Three Vania br Tambunan; Hani Auliya Simanjuntak; Novita Sari Sihombing; Dayana Rebecca Tampubolon (Journal of Cultural and Innovative Education, 2026)
This study aims to analyze the relationship between import spending and the savings levels of students in the Economics Education Study Program, batch 2024, HKBP Nommensen University. Import spending in this study refers to students' spending on foreign products, both directly and through digital platforms. Meanwhile, student savings reflect an individual's ability to manage their finances and set aside a portion of their income or pocket money. The research method used was a quantitative approach with data collection through a questionnaire. The study sample consisted of Economics Education students, batch 2024, selected using a specific sampling technique. Data analysis was conducted using a correlation test to determine the relationship between the two variables. The results showed a significant relationship between import spending and student savings levels. The higher the level of import spending, the lower the student savings rate. This suggests that consumption patterns for imported products can influence student savings behavior. The conclusion of this study is the importance of student awareness in managing finances, particularly in limiting import spending to improve savings habits.